An analysis about the daily life and the domestic spaces at Athens (6th-4th centuries BC) - Guimarães Neto, Edson Moreira (Romanitas - Revista de Estudos Grecolatinos, 2018)
In this article, we will try to observe and analyze everyday life within the context of domestic spaces and how the lawful wives and courtesans (even as ritual agents) lived with the Athenian citizens in these places. Through working with the proposed documentation, we will take the spheres of coexistence and intragroup and intergroup social interaction processes to analyze similar points between the lives of Athenian women and hetairai, and thus elucidate how the discourse around the feminine matrix was operated for the conceptual construction of domestic life.